Silicon uptake ability of different rice genotypes and their tolerance to salt stress with silicon fertilization - Rupasinghe, Minninga Geethika Neranjani (2022)
Silicon (Si) has a wide range of beneficial impacts on rice (Oryza sativa L.) including mitigating salt stress. Planting of existing rice genotypes with Si fertilization is of great importance among the salt mitigation techniques. A series of experiments were carried out to investigate the Si uptake ability of popular indica type rice genotypes, Bw 367, At 362, Bg 359, Bg 360, Bg 94-1, and MR 297 and to explore their tolerance to salt stress with the provision of Si. Genotypic variation was observed in tissue Si concentration (μg/100 mg) ranging from 104.0 (Bg 94-1) to 151.0 (Bw 367) in the experiment conducted in nutrient solution using a split plot design. Silicon concentration of 2 mM was found as the adequate level for the highest Si accumulation and to improve plant growth. The different Si rates were tested with genotype Bw 367 in a pot experiment conducted in randomized complete block design. Basal application of Si at the rate of 100 kg SiO2/ha recorded the highest tissue Si concentration of 395.3 μg/100 mg and the highest uptake (mg/pot) of 1912.5, 291.7 and 424.6 for K, Mg and P, respectively resulting in the maximum yield of 104.6 g/pot. The estimated Si rate for optimum yield was 115 kg SiO2/ha. Two Si transporter genes, OsLsi2 and OsLsi6 were found in all the tested genotypes. The highest relative expression of OsLsi2 gene was observed in genotype Bw 367 (0.85) and the lowest in Bg 360 (0.38) which was similar to Bg 94-1(0.39). Consequently, Si content (μg/100 mg) in plant tissue followed the same trend with Bw 367 (153.07) and Bg 94-1 (105.05). Rice genotypes were tested in a split-split plot design with Si application revealed that Bw 367 and Bg 94-1 were tolerant and Bg 359, At 362, and MR 297 were moderately tolerant in the highest salinity level of 12 dS/m in solution culture. Accumulation of Si was comparatively higher in stressed plants (salinity level 12 dS/m), as indicated by genotypes Bw 367 and Bg 94-1 accumulating similar Si contents (about 228.00 μg/100 mg), where 3 and 16.4% reductions were observed in their shoot growth, respectively in contrast to the non-saline condition. Applied Si reduced the electrolyte leakage by 53% in Bg 94-1 and Na+/K+ ratio by 82% in Bw 367 even at a salinity level of 12 dS/m. Further, proline content and catalase activity were increased by 77 and 106%, respectively in Bw 367, which was statistically similar to Bg 94-1. Similar relative water content was observed in Si treated Bw 367, Bg 94-1 plants, and salinity resistant Pokkali plants which were about 70%. In conclusion, Si fertilization had promising effects on the amelioration of salt stress in indica rice genotypes which could accumulate more Si in saline conditions. Except for Bg 360, with Si fertilization, all tested genotypes could successfully be cultivated on marginal lands in saline or salinity-prone areas to keep sustainable rice production.